HYGIENIC ASSESSMENT OF THE RELATIONSHIP BETWEEN MICROCLIMATE, AIR POLLUTION, AND STUDENT WELL-BEING AT TASHKENT STATE MEDICAL UNIVERSITY (Educator Insights: Journal of Teaching Theory and Practice, 2026)
Air pollution and unfavorable indoor microclimate conditions represent major environmental health threats in rapidly urbanizing regions. University students constitute a vulnerable population due to prolonged exposure to enclosed educational environments with variable ventilation and pollutant accumulation. This article presents a structured scientific analysis based on the proposed study of hygienic relationships between indoor microclimate, air pollution, and self-reported well-being among students of Tashkent State Medical University (TSMU). The work integrates global evidence on air quality, microclimate hygiene, and student health with a proposed local investigation framework. The article outlines the scientific rationale, objectives, methodological design, expected outcomes, and public health implications. Particular emphasis is placed on particulate matter (PM2.5), gaseous pollutants, CO₂ concentration, volatile organic compounds (TVOCs), and thermal comfort parameters as determinants of fatigue, respiratory function, cognitive performance, and general well-being. The study contributes to environmental hygiene by bridging campus environmental monitoring with student health indicators, forming a model for sustainable academic infrastructure management